Enhancing computing studies in high schools: A systematic literature review & UAE case study. Issue 2 (February 2019) - Talib, Manar Abu; Einea, Omar; Nasir, Qassim; Mowakeh, Mohamad Fouzi; Eltawil, Mohamed
Abstract: Open source software (OSS) is increasingly being integrated into educational institutions, and many countries require the use of OSS in government departments. However, not much focus is placed on integrating it into the educational sector in a strategic and productive manner. This paper examines the existing literature on the use of OSS in terms of the potential enhancements it can provide for computer science studies in high schools in general, and those in the UAE more specifically. It also details a survey conducted among 400 high school teachers after teaching them about multiple types of OSS that might enhance their teaching experience. After examining more than 69 different research papers and taking the survey findings into account, we drafted a roadmap that can be used by any educational institute—especially high schools—to strategically integrate OSS into the educational system.